2017
DOI: 10.1038/onc.2017.68
|View full text |Cite
|
Sign up to set email alerts
|

MRL proteins cooperate with activated Ras in glia to drive distinct oncogenic outcomes

Abstract: The Mig10/RIAM/Lpd (MRL) adapter protein Lpd regulates actin dynamics through interactions with Scar/WAVE and Ena/VASP proteins to promote the formation of cellular protrusions and to stimulate invasive migration. However, the ability of MRL proteins to interact with multiple actin regulators and to promote serum response factor (SRF) signalling has raised the question of whether MRL proteins employ alternative downstream mechanisms to drive oncogenic processes in a context-dependent manner. Here, using a Dros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In ph tumors, co-expression of Bsk-DN reduces the volume of mutant clones [ 34 ]. Similarly, JNK activity is induced and co-expression of Bsk-DN can suppress tumorigenesis in Ras + Pico [ 96 ], Ras + Src [ 83 , 97 ], and activated N + Src [ 98 ] models. However, in some tumors, tumor growth and invasive potential can be uncoupled from each other.…”
Section: Analysis/resultsmentioning
confidence: 99%
“…In ph tumors, co-expression of Bsk-DN reduces the volume of mutant clones [ 34 ]. Similarly, JNK activity is induced and co-expression of Bsk-DN can suppress tumorigenesis in Ras + Pico [ 96 ], Ras + Src [ 83 , 97 ], and activated N + Src [ 98 ] models. However, in some tumors, tumor growth and invasive potential can be uncoupled from each other.…”
Section: Analysis/resultsmentioning
confidence: 99%
“…Moreover, a genetic screen of the kinome led to the identification of RIOK1 and RIOK2 kinases, which promote mTORC-Akt signalling to drive glial tumour growth [ 113 ]. A recent study has also revealed cooperative tumorigenesis in glial tumour growth and invasion between Ras V12 and overexpression of pico (a MRL family gene), chickadee ( profilin, encoding an actin-cytoskeletal regulator) or Mal (encoding a cofactor of Serum Response Factor (SRF)) [ 107 ], suggesting that SRF signalling might be a novel pathway to investigate in human glioblastomas.…”
Section: Cooperation Interactions Between Oncogenic or Tumour-suppmentioning
confidence: 99%
“…Finally, YETI protein has also been implicated in cell cycle control in both mitosis and meiosis (Billmann et al, 2016). According with these results, it has been reported that Myc, a well-known oncogenic player (Bellosta et al, 2005; Jonchere et al, 2017; Taylor et al, 2017), and the DOMINO ATPase interact each other and are required for normal asymmetric neuroblast (NB) division. Live-imaging analysis of dom -or myc -depleted NBs showed that spindle morphology is affected resulting in aberrant divisions (Rust et al, 2018).…”
Section: Emerging New Functions Of Yeti and Its Orthologsmentioning
confidence: 97%